Angular momentum and landing efficiency in the long jump - Bouchouras, G.; Moscha, D.; Papaiakovou, G.; Nikodelis, T.; Kollias, I. (European Journal of Sport Science, 2009)
The purpose of this study was to compare the amount of angular momentum and the efficiency of landing for the hang and 2 hitch kick long jump techniques. Twelve male long jumpers participated in this investigation and were divided into two groups based on their flight technique (hang group, n=6; hitch kick group, n=6). The participants performed three jumps with full run-up, the best of which was selected for analysis. A two-dimensional DLT analysis of the take-off, flight, and landing was conducted for the two groups. Three cameras (JVC GR-DVL 9800 GL, Victor Company, Japan) with a sampling frequency 50 Hz were used. Two of the cameras were placed perpendicular to the run-up, on the right and left side of the take-off board, to record the take-off and the flight of the athletes (from both sides of the movement); the third was placed perpendicular to the pit, on the right side, to record the landing. The two groups differed in their angular momentum at the instant of take-off (hang: -11.92 kg·m2·s-1; hitch kick: -22.69 kg·m2·s-1; P<0.001) in the front direction, and in linear and angular velocity, mainly of the arms, at the instant of take-off. According to the results, the 2 hitch kick group had greater angular and linear velocities (P<0.05). The 2 hitch kick group had better landing efficiency than the hang style group (P<0.05), as the athletes in the former group managed to land their pelvis in front of their heels during landing. On the other hand, the hang style group landed their pelvis almost 5.81 cm behind the heels during landing and shortened their final distance. It seems that the 2 hitch kick group had better landing efficiency because of their greater amount of angular momentum. The hang style group could have achieved better landing through an increase in angular momentum, which depends on an increase of the linear and angular velocities of the two arms during take-off.